An effective discrete model for strain hardening cementitious composites: Model and concept. (June 2017) - Shi, Tiansheng; Leung, Christopher K.Y.
Highlights: Based on physical process of multiple cracking, a new discrete model is proposed for SHCC. The proposed model can effectively and efficiently simulate the realistic multiple cracking behavior of SHCC. The improved model can reproduce almost every aspect of crack pattern in SHCC. Efficient and accurate, the proposed model should be useful in analyzing structural member made of SHCC. Abstract: Strain hardening cementitious composite (SHCC) are materials exhibiting high deformation capacity and excellent crack control. In applications where SHCC is employed to enhance durability, information on the crack width and spacing under loading is important. In conventional finite element analysis, the material is commonly modeled as a continuum with tri-linear tensile behavior, which cannot capture the crack pattern. Here an efficient discrete model for SHCC is proposed to address such an issue, with the use of continuum element for matrix damage/cracking, truss element for fiber bridging effect and interface element for matrix-fiber interaction. Appropriate constitutive laws are assumed for these elements and the parameters are calibrated from direct tensile test. The validity of the model is shown by analyzing a tensile specimen and the realistic multiple cracking process of SHCC is captured. Through a systematic parametric study, the effects of important model parameters on the tensile behavior of the composites are assessed. The proposed model is further improved to accurately reproduce the evolution of crack pattern, including average and maximum crack width, crack density and crack width distribution. Efficient and accurate, the model can be used for analysis of SHCC members under bending, restrained shrinkage or subject to reflective cracking.